O gesto crítico-performativo do/a artista docente em dança: investigações com artistas docentes de dança no estado do Rio Grande do Sul - Santos, Oneide Alessandro Silva dos (2022)
This study presents reflections on the vocabulary that constitutes and de-shapes the idea of an artist teaching or teaching artist in dance. For this, the dissertation consists of two main parts, the first concerns the theoretical framework that seeks to highlight the importance of the theme for dance and education from a detailed survey in national repositories. The second enables the experimental and unpublished part of the investigation, in which it narrates the trajectory of three dance teaching artists in the state of Rio Grande do Sul, through interviews, reflection on their works and dance practices. The participants of this investigation were Eva Schul from Porto Alegre, Alline Fernandez from Santa Maria and Matheus Brusa from Caxias do Sul. As guiding problems arise: what critical-performative gestures constitute the dance teachers artists in the state of RS, especially those who work in spaces of schools, collectives and dance companies? what dichotomies or in-between-places constitute these professionals? The methodological approach approaches Bricolage conceptions in a multi-referential, relational and historical operation, mainly to think/do an interdisciplinary research that talks to several authors and theories. Critical-performative pedagogy is established in the sense of conducting the methodological, epistemological and conceptual arrangements of research. Bricolage and critical-performative pedagogy work as elastic approaches, allowing openings and cracks to build research in education that is separate from those canonized. It is concluded that experience seems to be the thread that leads these teaching artists in a life-work guided by practice, orality, body to body, by the gesture of teaching, creating and transmitting possibilities of experience. It is therefore an embodied practice of gestures, stutters, accents, markings, clicks, attempts and encounters with each other. It is a gesture always in relation to the other, but that in a way reflects itself and its predecessors.